Autogenous self-healing of low embodied energy cementitious materials: Effect of multi-component binder and crack geometry. (2nd May 2023) - Rajczakowska, Magdalena; Tole, Ilda; Hedlund, Hans; Habermehl-Cwirzen, Karin; Cwirzen, Andrzej
Highlights: Self-healing of ternary and quaternary binders at an early age was tested. 50 wt% of cement was replaced with limestone, fly ash, slag, and silica fume. The relation between chemical composition, crack geometry, and recovery was studied. A combination of limestone and slag exhibited the most pronounced self-healing. Ca(OH)2 and CaCO3 demonstrated a moderate correlation with self-healing indexes. Abstract: Concrete's ability to auto-repair the cracks reduces the need for maintenance and repair. Autogenous self-healing is an intrinsic property of concrete highly dependent on the binder composition. The urgent necessity to decrease CO2 emissions of concrete by replacing cement with "greener" materials provides challenges and opportunities for self-healing cementitious materials. This research aims to verify the self-healing behavior of environmentally friendly multi-component binders. An experimental study is conducted to test the effect of binder composition-related parameters (e.g., phase composition, porosity) and crack geometry on the self-healing efficiency of the "green" mortars. Cementitious materials with 50 wt.%cement replacement with limestone powder blended with fly ash, blast furnace slag, and silica fume are investigated. Sorptivity change, compressive strength regains, and crack closure after self-healing are used to quantify the self-healing efficiency. Quantitative analysis and correlations between chemical composition/microstructural features, geometrical crack characteristics, and self-healing measures are investigated. The results indicate that "green" binder composition affects the self-healing mechanism leading to different levels of performance recovery. Some SCMs-limestone binder formulations enable a better self-healing efficiency than pure OPC or OPC/limestone cementitious materials, presumably due to a synergistic effect between the limestone and the mineral additions. Correlation analysis indicated that geometrical complexity characterized by fractal dimension and tortuosity of the crack does not affect the external crack closure, whereas the fractal dimension and maximum crack width are correlated with the internal crack healing.